Leveraging information technology to enhance financial inclusion in rural Algeria: A case study of the agricultural and rural development bank (BADR) in Jijel - Fatima, Larabi (International journal of economic perspectives, 2024)
This study aims to explore how information technology (IT) can be leveraged to enhance financial inclusion in rural areas, with a focus on the Agricultural and Rural Development Bank (BADR) in Jijel, Algeria. The research employs a mixed-methods approach, combining quantitative analysis through surveys and qualitative insights via semi-structured interviews with BADR employees and customers. The main tools for data analysis include statistical software for regression analysis and thematic analysis for qualitative data. The findings reveal a significant positive impact of IT on financial inclusion, demonstrating that IT enhances access to, utilisation of, and the quality of financial services in rural regions. Despite challenges related to outdated infrastructure and resistance to change, the study concludes that further investment in IT infrastructure and staff training is essential to fully realise the potential of IT in promoting financial inclusion in rural Algeria.